2020
DOI: 10.1115/1.4046530
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Surface Thermal Radiation on Heat Transfer in a Ventilated Cavity

Abstract: The influence of thermal radiation in heat transfer and air circulation inside offices and rooms is an aspect that has not been thoroughly studied yet. Therefore, it is commonly not considered in calculations for the adequate capacity of air-conditioning equipment and ventilation positions. Here, experimental and numerical results were obtained to analyze the effect of surface thermal radiation on heat transfer in a ventilated cavity. Experimental temperature profiles were obtained at six different depths and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Velusami et al 35 concluded that surface radiation interaction leads to more significant velocity magnitudes and turbulence intensities at the boundary layers, increasing convective heat transfer by 25%. Navarro et al 36 reached that experimental heat transfer coefficients showed a significant effect of thermal radiation. When the walls’ emissivity rose from 0.03 to 0.98, it went up significantly.…”
Section: Resultsmentioning
confidence: 97%
“…Velusami et al 35 concluded that surface radiation interaction leads to more significant velocity magnitudes and turbulence intensities at the boundary layers, increasing convective heat transfer by 25%. Navarro et al 36 reached that experimental heat transfer coefficients showed a significant effect of thermal radiation. When the walls’ emissivity rose from 0.03 to 0.98, it went up significantly.…”
Section: Resultsmentioning
confidence: 97%
“…El-Sherbiny et al [5] and Kim et al [6] numerically verified that the wall surface emissivity of a cavity affects its heat transfer dramatically. Based on different numerical methods, references [7][8][9][10][11] indicate that the average Nu increases with increasing surface emissivity in a cavity. References [12][13][14][15] investigated the relationship between the radiation effect and the heat transfer in the cavity based on different numerical models.…”
Section: Introductionmentioning
confidence: 99%